Immuno-informatics insight into the relationship between cholesterol and cytokines in cutaneous leishmaniasis: from clinics to computation - Karimi, Ishaq; Thanun, Ala H.; Muhammad, Layth J.; Sulayman, Evan H. (Sultan Qaboos University medical journal, 2024)
Objectives: The role of serum cholesterol and its interactions with cytokines in human cutaneous leishmaniasis (CL) pathophysiology is unknown. This study aimed to evaluate the correlation among serum total cholesterol (TC), very-low-density lipoprotein cholesterol (VLDL-C), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), triglycerides (TG) and cytokines (including interleukin [IL] 10), IL-12 and tumour necrosis factor-alpha [TNF-α]) in CL. The cholesterol–cytokine network was analysed to illuminate the pathogenesis of CL. Methods: This case-control study was conducted from December 2022 to March 2023 in hospitals within Baghdad and Wasit provinces, Iraq, and included CL and CL-free subjects ranging between 20–30 years of age. The serum samples were analysed via commercial kits to detect TC, IL-10, IL-12, TNF-α, VLDL-C, LDL-C, HDL-C and TG levels. Computational efforts to dissect cholesterol-protein interaction networks were employed using STITCH. Results: A total of 50 CL and 25 control subjects were included. The TC, HDL-C and LDL-C levels in CL patients were markedly lower (P = 0.0001) than in control subjects, whereas the IL-10, IL-12, TNF-α, VLDL-C and TG levels were higher in CL patients. Serum cholesterol showed no correlation with cytokines; however, a significant correlation (r = 0.57; P = 0.026) was observed between IL-12 and TNF-α. Within the cholesterol-protein network, cholesterol potentially interacted with IL-10, connecting cholesterol to modules with immunological significance, including TRAF1, TRAF2 and TNF receptor superfamily member 1B, as well as IL-10, IL-10RA and IL-12RB1. Conclusion: This study showed the alteration of lipid and lipoprotein in CL and introduced 2 immunological modules in CL, highlighting the importance of the altered cholesterol-cytokine interaction network in CL.